ANALISIS PENGARUH CAPITAL REQUIREMENT TERHADAP KINERJA BANK (STUDI KASUS PADA BANK-BANK YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2005-2011) - , Yenofiar ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Bank performance as a financial institution is interested for many people because of the functions and roles of a bank in the economic system comprehensively. Competitive marketing strategies as a factor of growth and success determine banking business, it is be more to be analysed for banks who entered the stock exchange and stock markets. This is because a higher competitive levels emerged as a result of the many businesses that went to the stock exchange and stock market are not only derived from the bank as a financial institution. The purpose of this study was to analyze the effect of capital ratio, capital dummy, efficiency, central bank reserves, liquidity, bank size, inflation, and the market capitalization toward bank's performance. The method is used in this research is explanatory research with hypothesis testing with quantitative approach. Sampling method used was non-probability sampling with a purposive sampling technique. The sample in this study is the banks listed on the Indonesia Stock Exchange the period 2005 to 2011. The data in this study is a secondary data obtained from Bank Indonesia, www.bi.co.id. The data were obtained from The research results were analyzed by using multiple linear regression with the help of Eviews statistical program version 7. The results showed that the variable capital ratio, capital dummy, and efficiency proven effect on return on equity (ROE), while the variable reserves, liquidity, bank size, inflation, market capitalization proved to have no effect on return on equity (ROE). Then the variable capital ratio, capital dummy, efficiency, reserves, and inflation proved to have no effect on the net interest margin (NIM), while the variable liquidity, bank size and market capitalization proven effect on the net interest margin (NIM).